2021
DOI: 10.3390/chemosensors9070166
|View full text |Cite
|
Sign up to set email alerts
|

Leftover Kiwi Fruit Peel-Derived Carbon Dots as a Highly Selective Fluorescent Sensor for Detection of Ferric Ion

Abstract: Recently, the use of natural products for the synthesis of carbon dots (CDs) has received much attention. Herein, leftover kiwi (Actinidia Deliciosa) fruit peels were successfully turned into beneficial fluorescent carbon dots (KN-CDs) via the hydrothermal-carbonization route. KN-CDs 1 and KN-CDs 2 were prepared without and with ammonium hydroxide, respectively. KN-CDs 1 and KN-CDs 2 were systematically characterized by various analytical techniques. Synthesized KN-CDs showed spherical-shaped morphology with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…The high-resolution C 1s spectra show the presence of sp 2 C (C=C), sp 3 C (C–C/C–N/C–O) and C=O/O=C–OH groups in these CDs ( Figure 3 b). The deconvoluted five peaks of the C 1 spectra are appropriately located at ~284.6, ~286.1, ~287.5, and ~288.7 eV and are ascribe to the C–C/C=C, C–OH/C–N/C–O, C=O, and O=C–OH groups, respectively [ 52 , 53 ]. Three types of N doping can be affirmed in these CDs by the high-resolution N 1 spectra ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution C 1s spectra show the presence of sp 2 C (C=C), sp 3 C (C–C/C–N/C–O) and C=O/O=C–OH groups in these CDs ( Figure 3 b). The deconvoluted five peaks of the C 1 spectra are appropriately located at ~284.6, ~286.1, ~287.5, and ~288.7 eV and are ascribe to the C–C/C=C, C–OH/C–N/C–O, C=O, and O=C–OH groups, respectively [ 52 , 53 ]. Three types of N doping can be affirmed in these CDs by the high-resolution N 1 spectra ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…Pu et al ( Pu et al, 2020 ) proposed a static quenching mechanism about the phenylalanine carbon dots (Phe-CDs), which kept its outstanding fluorescence intensity despite its extreme pH values. Atchudan et al ( Atchudan et al, 2021 ) reported that they synthesized fluorescent carbon dots (KN-CDs) by hydrothermal carbonization method as a good fluorescence sensor of Fe 3+ based on the closing sensor of Fe (III) ions. Ju et al ( Ju and Chen, 2014 ) synthesized environmentally friendly nitrogen-doped graphene quantum dots (N-GQDs) for the unlabeled Fe 3+ ions detection in various actual water ( Figure 2B ).…”
Section: Probes For Ironmentioning
confidence: 99%
“…ammonia ( Mondal et al., 2016 ) (plant source) Hydrothermal 2.5 1–90 Na (I), Al (III), Mn (II), Ag (I), Ni (II), Co (II), Zn (II), Cd (II), Hg (II), Mg (II), Pb (II), Cu (II), and Fe (III) Chionanthus retusus (C . retusus) fruit extract ( Atchudan et al., 2017 ) (plant source) Hydrothermal 70 0–2 9 Al (III), Ca (II), Cd (II), Co (II), Cr (III), Cu (II), Fe (II), Fe (III) , Hg (II), Ni (II), Pb (II), and Zn (II) Kiwi fruit peels + ammonium hydroxide ( Atchudan et al., 2021 ) (plant source) Hydrothermal 0.95 and 0.85 5–25 14 19 Al (III), Ca (II), Cd (II), Co (III), Cr (III), Cu (II), Fe (III) , Hg (II), Mn (II), Ni (II), Pb (II), and Zn (III) Betel leaves + aq. ammonia ( Atchudan et al., 2019 ) (plant source) Hydrothermal 0.135 0.3–3.3 4.21 K (I), Cu (I), Na (I), Pb (II), Cu (II), Cr (VI), Zn (II), Fe (II), Cd (II), Ag (I), Fe (III) , Hg (III), and Mn (III) Curauá (Ananas erectifolius) fibers ( Raja et al., 2021 ) (plant source) Hydrothermal 0–30 0.77 Fe (III) , Na(I), K (I),Mg (II), Ca (II), Ba (II), Cr (II), Mn (II), Fe (II), Co (II), Ni (II), Cu (II), Ag (I), Zn (II), Cd (II), Hg (II), and Al (III) Ripe banana peels + ethylene diamine + L-cysteine ( Das et al., 2021 ) (plant source) Hydrothermal 10–200 ×10 −6 121 × 10 −6 27 Fe (III) , Hg (II), Cu (II), Cr (VI), Cd (II), Mg (II), Na (I), and K (I) Biomass waste (orange peel , ginkgo biloba leaves , paulownia leaves, and magnolia flower) ( Wang et al., 2020a ) (mixture of 4 different plant sources) Hydrothermal 0.088 (MF-CQDs) 0.2–100 8.13 Ag (I), K (I), Na (I), Pb...…”
Section: Carbon Dots For Heavy Metal Ion Detectionmentioning
confidence: 99%
“…Two FL CDs were prepared using leftover kiwi fruit peel without and with ammonium hydroxide (NH 4 OH). Reduced fluorescence intensities of the CDs (to nearly zero) were attributed to the complex formation because of the stronger affinity of CDs with Fe (III) ions ( Atchudan et al., 2021 ). N-CDs made from betel leaves and ammonia revealed blue fluorescence and exhibited good selectivity and sensitivity to picric acid and Fe (III).…”
Section: Carbon Dots For Heavy Metal Ion Detectionmentioning
confidence: 99%